Sosialisasi Penyelenggaraan Pendidikan Inklusif Di SMK Negeri Rawas Ulu Kabupaten Musi Rawas Utara - Nurwahyuliningsih, Eka; Ramdani, Jaka (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – This activity aims to provide information and increase understanding to students and schools about inclusive education, as well as provide support for the implementation of inclusive education programs in schools. Design/methodology/approach – The implementation method uses socialization, with several stagncluding the planning stage, preparation stage, implementation stage, and evaluation and mentoring stage. Socialization activities were carried out at SMK Negeri Rawas ulu, North Musi Rawas Regency, attended by all grade X (ten) students from various departments. Findings – Results The inclusive education program aims to increase access to quality education services that are appropriate for children with special needs and are able to guarantee children the right to education that is equal to other children. The transformation of the education system towards inclusive schools in all regular schools is one of the government programs that is currently being pursued so that it can be implemented properly, including at SMK Negeri Rawas Ulu in North Musi Rawas Regency. With the socialization activities, students can find out information about the inclusive education system and the concept of children with disabilities including the definition of disabilities, various disabilities, facilities and infrastructure that are accessible to people with disabilities, characteristics of children with disabilities, obstacles experienced by people with disabilities; as well as introducing an inclusive environment that is friendly to children with disabilities without discrimination at school. In addition, schools will support and encourage the implementation of inclusive education by developing policies, training teachers, providing infrastructure, developing curriculum and developing an inclusive culture. Originality/value – Overall, socialization activities have a positive impact not only for schools but also for students, one of which is fostering students' concern for people with disabilities in the school environment and residence and manifesting a disability-friendly school environment.